Keputusan Pemilihan Karir: Studi Komparatif pada Siswa Remaja Jurusan IPA dan IPS - Fatma Nuraqmarina; Erna Risnawati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2018)
The purpose of this study was to compare career choice decisions between students majoring in Science and Social Sciences. This study used the comparative quantitative method. The subjects were 188 students, consists of 94 students on each major in Science and Social Science. The subjects were selected by purposive sampling, with the characteristics of class XII students majoring in science and social studies and aged 15-18 years. The data were analyzed using Mann-Whitney Nonparametric Test. The findings showed that there were no significant differences in career choice decisions between students majoring in Science and Social Sciences. There were 39 science and 53 social sciences students who have difficulties in deciding their careers.